Regulasi diri dan prokrastinasi akademik siswa Sekolah Menengah Kejuruan (SMK) - Moh. Zainurridla; Mohamad Aso Samsudin; Fauzul Adim Ubaidillah (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2022)
This study aims to obtain empirical evidence the role of self-regulation on student's academic procrastination. The research method used is correlational quantitative. The sample in this study amounted to 120 students who came from students of SMK Ibrahimy 2. The scale used was Tuckman and Zimmermant. The method used to analyze the data in this study is to use statistical analysis methods using the Spearmen Test and Test . To simplify the calculation, the JAMOVI program is used. Based on the output of the hypothesis test results, the value is known, the significance value is p = 0.009 (<0.001) it can be interpreted that there is a relationship between self-regulation and academic procrastination. The results of the hypothesis test on Spearman's rho resulted in a value of -0.215, from the results of the correlation coefficient test it was known that the relationship between self-regulation variables and academic procrastination was a negative relationship.